Evaluation of Distolingual Canal/Roots in Mandibular Molars and Mesiobuccal Canals in Maxillary Molars by CBCT - DUMLU, ASIM; NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (BENTHAM SCIENCE PUBL LTD, 2017)
Background/Purpose: The objectives of this study were to identify the bilateral distolingual (DL) canals / roots of the mandibular first molars and second mesiobuccal (MB2) canals of the maxillary first molars in the same Turkish individuals using cone-beam computed tomography (CBCT). Materials and Methods: A total of 150 CBCT images including all mandibular and maxillary first molars were retrospectively investigated in a Turkish subpopulation. The patient age, sex and presence of roots and root canals were assessed. The frequency, of bilateral DL canals, DL roots, and MB2 canals were reviewed. Data were analyzed using Fisher'sexact test and Chi-square test. Results: The prevalences of right DL canals, DL roots and MB2 canals were 31.3, 14.0 and 34.7%, respectively. The prevalences of left DL canals, DL roots and MB2 canals were 31.3, 4 and 27.3%, respectively. There was no statistically difference in the frequency of right and left DL canals, DL roots of mandibular first molars and MB2 canals of maxillary first molars according to gender. Conclusion: CBCT is a competent tool for the detection of additional distolingual canals/ roots and second mesio buccal canals, and it is a valuable aid for dentists providing root canal treatment.
Keywords: CBCT; Endodontic treatment; Root canal; Molar; Mesiobuccal Canal; BEAM COMPUTED-TOMOGRAPHY; 1ST MOLARS; CHINESE POPULATION; PERMANENT MOLARS; ROOT CANALS; CONFIGURATION; PREVALENCE; MORPHOLOGY; ANATOMY